Le Perroquet de Flaubert de Julian Barnes : genèse d’une passion littéraire - Vanessa Guignery (Flaubert: Revue Critique et Génétique)
Based on the archives of the British writer Julian Barnes relating to Flaubert’s Parrot (1984), the paper proposes to explore several elements of the genesis of this transgeneric book as well as some aspects of the creative process in order to determine the ways in which Barnes chose to approach Flaubert’s work and life. The writer’s travel notebooks, notes, plans and drafts, as well as the letter he sent his editor to defend his manuscript, shed light on the original means chosen by Barnes to celebrate Flaubert while diverging from traditional biographical and critical approaches.